Inhibition of TrkB Limits Development of the Zebra finch Song System - Beach, Linda Qi (Brain Res, 2016)
Large sexual dimorphisms exist in the zebra finch song system. Masculinization may be mediated by both estradiol and expression of one or more Z-genes (males: ZZ; females: ZW). Roles of the Z-gene tyrosine kinase B (TrkB) in HVC in masculinizing both it and its target the robust nucleus of the arcopallium (RA) were tested using siRNA administration in juvenile males at two ages (post-hatching days 15-17 or 25-27). Birds were euthanized 10 days later. Potential interactions or additive effects with estradiol were evaluated by treating males with the estrogen synthesis inhibitor fadrozole. Females treated with estradiol were also exposed to the siRNA at the later age. Local inhibition of TrkB in males of both ages reduced the volume of HVC, an effect due to a change in cell number and not cell size. In the older males, in which the treatment spanned the period when the projection from HVC to RA grows, TrkB inhibition reduced the volume of RA and the relative number of cells within it. TrkB siRNA in HVC decreased the volume of and soma size in the RA of females, and the projection from HVC to RA in both sexes. Estradiol in females masculinized various aspects of the song system, and its effect in masculinizing the volume of RA was decreased by TrkB inhibition. However, effects of fadrozole in males were limited. The data indicate that TrkB is involved in masculinizing the song system, but for most measures it probably does not work in concert with E2.